Selbstschutz: associativismo colonial e a experiência da autodefesa nas colônias teuto-brasileiras do Rio Grande do Sul (1890-1930) - Adam, Paulo Rogério Friedrichs (2020)
This research focuses on the trajectory and the changes of the German-Brazilian settlers membership organization in Rio Grande do Sul, mainly that political and self-protection membership that existed from the end of the 19th century to the first third of the 20th century. For this purpose, a problem was formulated corresponding to the trajectory of this partnership and how it connects to the proposal of an overarching organization and what the role of the organization of a self-defense movement (Selbstschutzverein) was in this process. It will be assumed that amidst these complex relations of the settlers with the sociopolitical reality, on the way to its political autonomization, there is a connection that links the history of the membership that evolved in the colonial region, involving the setting up of the Colonial Party (Koloniepartei) and the Colonial Associations (Kolonieverein), going through the Riograndense Farmers Association (Bauernverein) to the Selbstschutzverein and the constitution of the Colonial Unions; a process in which the setting up of the Selbstschutzvereine in the 1920s was essential, in the highland region. It is argued the thesis that the Selbstschutzvereine from the 1920s played a pivotal role in the rearticulation of the colonial membership around the proposal of a large association of settlers, converging to the setting up of the Colonial Union, this is because the organizing efforts that they represented enabled an important buildup in the form of leaderships and organizing structures. The space contour involves the settlement region from Rio Grande do Sul, known as old and new settlements, while the time covers the period from 1890 to 1930, coinciding with the beginning of the republican period in Brazilian history with the emergence of the Koloniepartei, and its catholic "cousin", the Center Party (Zentrumpartei). The final demarcation of the study period is also given by the end of a period in Brazilian history, with the Revolution of 1930, what is coincident with the structuring of the Colonial Unions as a state movement, occurring as of 1929, when, in the city of Santa Maria, the Alliance of the Colonial Unions from Rio Grande do Sul was founded. The Thesis was developed by means of a documental and bibliographic research, with the reading, analysis and compilation of the primary and secondary documentation, followed by the critical analysis of the information collected, based on the historiographic literature. The Thesis features a contribution to be made in the field of the migration history, aimed at the study of the membership movements of settlers, since there are few researches about the political and self-protection membership and there is not, in known researches, an explanation of the connection between the colonial party, the colonial associations, the setting up of the Selbstschutzvereine and the Colonial Unions. Specifically, the subject of the Selbstschutzvereine is practically unheard.